2021
DOI: 10.1186/s12915-021-01017-0
|View full text |Cite
|
Sign up to set email alerts
|

Rat PRDM9 shapes recombination landscapes, duration of meiosis, gametogenesis, and age of fertility

Abstract: Background Vertebrate meiotic recombination events are concentrated in regions (hotspots) that display open chromatin marks, such as trimethylation of lysines 4 and 36 of histone 3 (H3K4me3 and H3K36me3). Mouse and human PRDM9 proteins catalyze H3K4me3 and H3K36me3 and determine hotspot positions, whereas other vertebrates lacking PRDM9 recombine in regions with chromatin already opened for another function, such as gene promoters. While these other vertebrate species lacking PRDM9 remain ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 78 publications
(134 reference statements)
1
8
0
Order By: Relevance
“…A possible explanation is that in the absence of the marks made by PRDM9, the machinery responsible for making DSBs defaults to residual sites of H3K4me3 (7) either because the mark causes its recruitment, say through a reader protein, or simply because such regions are more accessible. Consistent with the notion that species lacking PRDM9 rely on other H3K4me3 marks, when Prdm9 is knocked out in B6 mice or SHR rats, ~92% and ~99% of DSBs occur at residual sites of H3K4me3, respectively (6,7). The knockout experiments in mice and rats, alongside the report of a human mother homozygous for a nonfunctional PRDM9 (20), further indicate that in species with a complete PRDM9, there exists an alternative mechanism of recombination that can serve as a backup, albeit a less efficient one (7,8,21).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…A possible explanation is that in the absence of the marks made by PRDM9, the machinery responsible for making DSBs defaults to residual sites of H3K4me3 (7) either because the mark causes its recruitment, say through a reader protein, or simply because such regions are more accessible. Consistent with the notion that species lacking PRDM9 rely on other H3K4me3 marks, when Prdm9 is knocked out in B6 mice or SHR rats, ~92% and ~99% of DSBs occur at residual sites of H3K4me3, respectively (6,7). The knockout experiments in mice and rats, alongside the report of a human mother homozygous for a nonfunctional PRDM9 (20), further indicate that in species with a complete PRDM9, there exists an alternative mechanism of recombination that can serve as a backup, albeit a less efficient one (7,8,21).…”
supporting
confidence: 76%
“…The mechanisms that specify the genomic location of hotspots differ among species. In mice, humans, and other mammals, the gene PRDM9 (PR/SET Domain 9) plays a key role (2)(3)(4)(5)(6). In mouse and rat, outside of the pseudoautosomal region (6,7), almost all hotspot locations are determined by PRDM9 binding.…”
mentioning
confidence: 99%
“…PRDM9 is one of the rapidly evolving genes in reindeer and is involved in recombination events and epigenetic modifications [ 51 ]. Moreover, recent studies on mice and rats showed that PRDM9 has important roles in spermatogenesis and male fertility [ 41 , 52 ]. Similarly, other upregulated genes in male samples have diverse functions and may be linked to male infertility or spermatogenic failure ( DDX3Y ), mRNA splicing ( ZRSR2 ), lipid metabolism ( EIF2S3X ), circadian rhythm ( USP9X ), cell cycle regulation ( TXLNG ), and photoreceptor development/function ( NRL ).…”
Section: Resultsmentioning
confidence: 99%
“…Other considerations: During these investigations, we considered other elements of the HDR and crossover recombination pathways that might influence the success of various configurations; recombination hotspots and distances to chromosomal ends might contribute to efficiency. In the Sprague-Dawley rat, no hotspot maps are available; strain-to-strain differences are very large, so data from other strains are not applicable (Mihola et al, 2021). We examined the mouse recombination hotspot map from the c57BL derivative mouse line Hop2 -/- (Smagulova et al, 2011).…”
Section: Biochemical Activity Of Cas9 In the Testicular Cells Of Ratmentioning
confidence: 99%